Response to and outcomes of the Pfizer BNT162B2 vaccine in hemodialysis patients—A prospective observational study. Issue 2 (5th January 2022) - Al‐Muhaiteeb, Abdullah; AlSahow, Ali; Al‐Yousef, Anas; AlHelal, Bassam; Alrajab, Heba; Bahbahani, Yousif; dewidar, Noha; Fanous, George N. M.
Abstract: Introduction: COVID‐19 infection is associated with high mortality among hemodialysis patients. Standard vaccine response is generally lower among these patients. The adequate antibody titer response and the outcome of COVID‐19 vaccine responders versus non‐responders are unknown. Methods: Hemodialysis patients on maintenance hemodialysis who have received two doses of Pfizer BNT162B2 vaccine were studied. Antibody response was tested after 14 days of the second dose. LIAISON SARS‐CoV2 S1/S2 IgG test by DiaSorin (Italy) was used to assess antibody response. Patients were followed between 3 and 7 months after vaccination for COVID‐19 infection, hospitalization and death related to COVID‐19. Findings: A total of 138 patients received two doses of Pfizer BNT162B2 vaccine. One hundred and twenty‐seven patients had adequate response to the vaccine with IgG level ≥ 15 AU/ml versus 11 patients had poor response with IgG level ≤ 15 AU/ml. The response was 92% (127/138). Patient with history of prior COVID‐19 infection had higher antibody titer mean of 339 ± 113 versus 157 ± 140 for patient with no prior history of COVID‐19. Seven patients in both groups had COVID‐19 infection post vaccine. Among the responders, five patients had COIVD‐19 infection and two were hospitalized. These two patients had lower antibody titer of 23.9 and 75.2 AU/ml. In comparison, three patients who were not hospitalized had higher antibody titer 96.3, 118, and 319 AU/ml, respectively. In the non‐responders one patient was hospitalized and one death occurred with rate of infection of 18%. Discussion: Seropositive patients with low antibody titer might be associated with worse outcome among responders. The ideal antibody titer level among dialysis patient is not known. Also, prior COVID‐19 infection is associated with higher response to vaccine with higher antibody titer. All non‐responders did not have prior COVID‐19 infection. More research is required to further evaluated protective antibody titer.